Pharmacist-led multidisciplinary approach in preventing strokes in people with atrial fibrillation. (2nd July 2022) - Patel, M; Ali, S; Robson, J; Clements, R; Theodoulou, A; Wright, P; Kearney, M; Patel, R; Sohaib, A; Antoniou, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: In England, 90% of patients with atrial fibrillation (AF) are expected to receive anticoagulation as part of targets set by Public Health England by 2029. In 2019/2020, across three London boroughs serving a population of 770, 000, the percentage of AF patients at high risk of stroke (CHA2DS2VASc>2) anticoagulated was 87%, 83% and 84%. This placed two of the three localities in the bottom 10% compared to others in England. In addition, optimising cholesterol and lifestyle choices can significantly reduce the risk of cardiovascular disease and associated mortality in these patients. Purpose: To prevent AF-related strokes by improving anticoagulation rates and optimising cardiovascular risk factors in patients with AF in all general practices across three London boroughs over one year, and to minimise risk of bleeding in patients on concurrent anticoagulation and antiplatelet therapy. Methods: A specialist cardiovascular pharmacist was commissioned to systemically identify high-risk AF patients (CHA2DS2VASc>2) by working with primary care clinicians, including up-skilling of primary care pharmacists. Through utilisation of 'proactive care frameworks' created by the Clinical Effectiveness Group Queen Mary University of London and UCL Partners, patients were able to be stratified and prioritised for review. AF patients not on anticoagulation or on antiplatelet monotherapy were deemed to be at highest risk, and these patients were reviewed to assess suitability for anticoagulation. Subsequently, patients on concurrent anticoagulation and antiplatelets were assessed to determine if dual antithrombotic prescribing was still indicated to minimise risk of major bleeding. Lastly, to optimise cardiovascular risk prevention, all AF patients were reviewed for suitability of statin initiation for primary or secondary prevention. A virtual multidisciplinary team was convened for complex patients, which included a cardiologist, haematologist, general practitioner and pharmacist to review and agree an action plan. Results: An interim analysis at 9 months reported that 94% (6745/7145) of patients with a CHA2DS2VASc>2 across the three boroughs were suitably anticoagulated, an improvement of 6% on the initial 88% (6585/7391). There was a reduction in concurrent anticoagulation and antiplatelet therapy from 381 to 262 patients (31.2% reduction) following specialist review. Lastly 2285 patients were reviewed with a recommendation to start a statin for either primary (n=1783) or secondary prevention (n=502). Conclusion(s): Provision of a specialist cardiovascular pharmacist supported a multidisciplinary workforce with significant improvement in anticoagulation rates across all three boroughs, reducing the risk of stroke in this high-risk population. In addition, we were able to reduce the risk of bleeding in this cohort of patients by stopping inappropriate antiplatelet therapy, and reduced the risk of cardiovascular disease through statin initiation.